PENGEMBANGAN MODUL UNTUK MENINGKATKAN SELF EFFICACY SISWA KELAS VII SMPN 5 CIMAHI - Reswari, Yassinta Alhumaira; Rohaeti, Euis Eti; Septian, Muhammad Rezza (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
This article aims to determine the feasibility and effectiveness of the module to This article aims to develop a module to improve the self-efficacy of class VII students of SMPN 5 Cimahi. The subjects in this study were 26 students of class VII and 3 validators to test the feasibility of the module. This study uses the R&D (Research and Development) method by going through 9 stages. The data analysis used is a feasibility test to determine the feasibility of the module that will be used to improve student self-efficacy and the t-test test used to determine the effectiveness of the module to increase self-efficacy. Based on the results of the feasibility test, it was stated that the module was in the "very feasible" category to be used as a medium for implementing guidance and counseling services with a score of 94.6% from material experts, 96.6% from media experts, and 82.3% from practitioners ( guidance and counseling teacher). In addition, the results of the feasibility test limited to students also obtained a score of 79.4% and the broad feasibility test with a score of 87%. Based on these results, the module can be used as a medium for implementing guidance and counseling services in schools. Looking at the results of the module effectiveness test to increase self-efficacy, it also has a significant result of 0.00 <0.05, which means that through the media module, the self-efficacy of class VII students can increase.